PERAMALAN KINERJA PERUSAHAAN PERBANKAN TAHUN 2017 YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN METODE ARCH-GARCH - Wijaya, John Henry; Nugraha, Nugi Mohammad (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2020)
This study aims to determine how the forecasting of banking stock performance in 2017 is measured weekly using the ARCH-GARCH method. There were 43 registered banking companies listed on the Indonesia Stock Exchange, but only 39 companies used as the research sample based on data completeness. The ARCH-GARCH method was used in the forecasting process. Results showed that the value of the mean absolute per cent error was 8.52% or below 10%. Therefore, the ARCH-GARCH method was quite good at predicting the performance of the banking sector. With a high level of complexity, the ARCH-GARCH method could provide a more realistic description than other methods to help investors make decisions. The banking sector tends to experience a downturn. Thus, it would be better for investors to hold back the intention to invest in banking stocks unless they are the risk-takers. Keywords: ARCH-GARCH, banking sector, stock performance